TINJAUAN YURIDIS PENERAPAN DEPONERING SEBAGAI ALASAN PELAKSANAAN ASAS OPORTUNITAS OLEH JAKSA AGUNG REPUBLIK INDONESIA - INTAN PURNAMA SARI; Dessy Artina; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Opportunity principle is a prosecution discretion owned by the Attorney General's Office which in this case only exists with the Attorney General through Law No. 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia, clearly authorizing the Attorney General to override cases in the public interest or what is called deponering. The Criminal Procedure Code also recognizes the existence of the principle of opportunity contained in the explanation of Article 77 of the Criminal Procedure Code. The purpose of writing this thesis is: First, to find out the application of deponering by the Attorney General of the Republic of Indonesia in the Criminal Procedure Code. Second, to find out the application of deponering as a reason for implementing the principle of opportunity by the Attorney General of the Republic of Indonesia. Third, to find out the ideal concept of deponering arrangements in the upcoming Criminal Procedure Law.This type of research can be classified in the type of normative legal research, because in this study the authors conducted research by examining library materials. The data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials, because the authors conduct research on the principles of law by utilizing descriptive methods to provide an overview of the application of case adjudication in the public interest (deponering) based on principle of opportunity.From the results of the study it can be concluded, First, the application of deponering by the Attorney General of the Republic of Indonesia is regulated in the explanation of Article 77 KUHAP. Secondly, the application of deponering as the reason for the implementation of the principle of opportunity by the Attorney General of the Republic of Indonesia is based on 3 (three) reasons, namely: Cases are set aside due to policy reasons; the criminal act was light, the perpetrator was old, the damage had been repaired and the loss had been replaced, the case was ruled out for technical reasons (insufficient evidence, past time, etc.) and the case was ruled out through a merger, which was to combine the case of the suspect with another case that had been brought to court . Third, the ideal concept of regulating deponering implementation in the upcoming procedural law is regulated in Article 42 Paragraph (2) of the KUHAP Bill. The author's suggestion, first, is more clarified in the technical stages of deponering, because the regulation on this matter is still unclear. Secondly, it is necessary to create guidelines that provide any criteria that are included in the public interest category. Third, it must have clear boundaries and parameters, namely the extent to which deponering meets the requirements in the public interest.Keywords: Deponering - Principle of Opportunity - For the Public Interest